The Future of Rome : Roman, Greek, Jewish and Christian Visions - Price, Jonathan J. (University of Cambridge ESOL Examinations, 2020)
Cover -- Half-title page -- Title page -- Copyright page -- Contents -- List of Contributors -- Acknowledgments -- List of Abbreviations -- Introduction -- Chapter 1 Some Remarks on Cicero's Perception of the Future of Rome -- Chapter 2 Eclogue 4 and the Futures of Rome -- Chapter 3 Imperium sine fine: Rome's Future in Augustan Epic -- Chapter 4 Posterity in the Arval Acta -- Chapter 5 The Future of Rome in Three Greek Historians of Rome -- Chapter 6 Philo on the Impermanence of Empires -- Chapter 7 From Human Freedom to Divine Intervention: Agrippa II's Address on the Eve of the Jewish War -- Chapter 8 Josephus, Caligula and the Future of Rome -- Chapter 9 "Will This One Never Be Brought Down?": Jewish Hopes for the Downfall of the Roman Empire -- Chapter 10 The Sibylline Oracles and Resistance to Rome -- Chapter 11 Revelation 17.1-19.10: A Prophetic Vision of the Destruction of Rome -- Chapter 12 Cicero and Vergil in the Catacombs: Pagan Messianism and Monarchic Propaganda in Constantine's Oration to the Assembly of Saints -- Chapter 13 The Future of Rome after 410 CE: The Latin Conceptions (410-480 CE) -- Appendix -- Bibliography -- Index Locorum -- Index of Names and Places.